2017
DOI: 10.1037/pac0000220
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Jewish–Palestinian mixed-model encounters on readiness for contact and policy support.

Abstract: Mixed-model encounters, focusing on both intergroup commonalities and status disparities, have become a popular intervention in efforts to improve relations between Jews and Palestinians within Israel. A quasi-experiment with Jewish and Palestinian encounter participants and nonparticipants as a control group (N ϭ 498) was conducted. Among Jews, the encounter enhanced readiness for contact by increasing empathy and hope and decreasing hatred. Elevated support for equal rights to Palestinian citizens was mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
(57 reference statements)
0
31
1
Order By: Relevance
“…Existing interventions that could achieve this are so-called mixedmodel encounters (Maoz, 2011;Zúñiga et al, 2002). These structured contact interventions build a climate of trust first, followed by an open discussion of privileges enjoyed by some and deprivations faced by others (Shani & Boehnke, 2017). Importantly, an open discussion of inequalities is essential to achieving social change because focusing solely on commonalities may decrease identification with the disadvantaged group (Dovidio et al, 2009;Ufkes et al, 2016) and draw attention away from group disparities (Dovidio et al, 2009;Saguy & Chernyak-Hai, 2012;Saguy et al, 2009;-Thiessen & Darweish, 2018).…”
Section: Implications Of Contact Interventions Aiming To Foster Sociamentioning
confidence: 99%
“…Existing interventions that could achieve this are so-called mixedmodel encounters (Maoz, 2011;Zúñiga et al, 2002). These structured contact interventions build a climate of trust first, followed by an open discussion of privileges enjoyed by some and deprivations faced by others (Shani & Boehnke, 2017). Importantly, an open discussion of inequalities is essential to achieving social change because focusing solely on commonalities may decrease identification with the disadvantaged group (Dovidio et al, 2009;Ufkes et al, 2016) and draw attention away from group disparities (Dovidio et al, 2009;Saguy & Chernyak-Hai, 2012;Saguy et al, 2009;-Thiessen & Darweish, 2018).…”
Section: Implications Of Contact Interventions Aiming To Foster Sociamentioning
confidence: 99%
“…Previous studies have examined Palestinians' readiness for personal or social engagement in intergroup contact with Israelis. Most of these studies, however, focused on the Israeli society, examining the relationship between the disadvantaged indigenous Palestinian minority and the dominant Jewish majority (Diab & Mi'Ari, 2007;Hofman, 1972Hofman, , 1982Peres, 1971;Sagiv & Schwartz, 1995;Shani & Boehnke, 2017;Smooha, 1984;Yogev, Ben-Yehoshua, & Alper, 1991;Yuchtman-Yaar & Inbar, 1986). These studies have typically shown that members of the indigenous Palestinians in Israel are more willing to establish relations with the Israeli Jewish than vice versa.…”
Section: Support For Normalization and Intergroup Relations Among Palmentioning
confidence: 99%
“…Existing interventions that could achieve this are so-called mixed-model encounters (Maoz, 2011;Zúñiga et al, 2002). These structured contact interventions build a climate of trust first, followed by an open discussion of privileges enjoyed by some and deprivations faced by others (Shani & Boehnke, 2017). Importantly, an open discussion of inequalities is essential to achieving social change because focusing solely on commonalities may decrease identification with the disadvantaged group (Dovidio et al, 2009;Ufkes et al, 2016) and draw attention away from group disparities (Dovidio et al, 2009;Saguy & Chernyak-Hai, 2012;Saguy et al, 2009;Thiessen & Darweish, 2018).…”
Section: Practice -How To Inform Practitioners?mentioning
confidence: 99%